Targeting Chk1 and Wee1 kinases enhances radiosensitivity of 2D and 3D head and neck cancer models to X-rays and low/high-LET protons - Emma Melia; Anne-Sophie Fisch; Ingeborg Tinhofer; Jason L. Parsons (Cell Death and Disease)
Abstract Ionising radiation causes the introduction of DNA damage, more specifically double strand breaks (DSBs) and complex DNA damage (CDD), that induces cancer cell death leading to the therapeutic effect. To combat this, cells activate arrest at the G2/M checkpoint to allow for effective DNA damage repair, coordinated by the Chk1 and Wee1 protein kinases. Therefore, Chk1 and Wee1 are considered promising therapeutic targets to enhance the effectiveness of radiotherapy in cancer cell killing. Here, we have analysed the response of head and neck squamous cell carcinoma (HNSCC) cell lines, spheroids and patient-derived organoids to X-rays and proton beam therapy (PBT) in the presence of either a Chk1 (MK-8776) or a Wee1 (MK-1775) inhibitor. We demonstrate that inhibitors of Chk1 or Wee1 can significantly enhance the radiosensitivity of both 2D and 3D models of HNSCC to X-rays and PBT (performed at both low and high ionisation densities), and that this effect is caused through abrogation of the G2/M checkpoint causing the persistence of DSBs. Our results therefore suggest that targeting Chk1 and Wee1 kinases in combination with X-rays and PBT could represent a promising therapeutic avenue to enhance the clinical efficacy of HNSCC treatment.